Effect of Periodontal Treatment on Glycemic Control of Diabetic Patients: A systematic review and meta-analysis - Teeuw, Wijnand J. (American Diabetes Association, 2010)
OBJECTIVE: There is growing evidence that periodontitis may affect general health. This study was assigned to explore the robustness of observations that periodontal therapy leads to the improvement of glycemic control in diabetic patients. RESEARCH DESIGN AND METHODS: A literature search (until March 2009) was carried out using two databases (MEDLINE and the Cochrane Library) with language restriction to English. Selection of publications was based on 1) original investigations, 2) controlled periodontal intervention studies where the diabetic control group received no periodontal treatment, and 3) study duration of ≥3 months. RESULTS: Screening of the initial 639 identified studies and reference checking resulted in five suitable articles. A total of 371 patients were included in this analysis with periodontitis as predictor and the actual absolute change in A1C (ΔA1C) as the outcome. The duration of follow-up was 3–9 months. All studies described a research population of type 2 diabetic patients in whom glycemic control improved after periodontal therapy compared with the control group (range ΔA1C: Δ−1.17 up to Δ−0.05%). The studies in a meta-analysis demonstrated a weighted mean difference of ΔA1C before and after therapy of −0.40% (95% CI −0.77 to −0.04%, P = 0.03) favoring periodontal intervention in type 2 diabetic patients. Nevertheless, this improvement in %A1C must be interpreted with care due to limited robustness as evidenced by heterogeneity among studies (59.5%, P = 0.04). CONCLUSIONS: The present meta-analysis suggests that periodontal treatment leads to an improvement of glycemic control in type 2 diabetic patients for at least 3 months.